Analysis of trimodal and bimodal therapy in a selective-surgery paradigm for locally advanced oesophageal squamous cell carcinoma. Issue 10 (5th June 2021) - Zhou, N; Mitchell, K G; Corsini, E M; Truong, V T T; Antonoff, M B; Mehran, R J; Rajaram, R; Rice, D C; Roth, J A; Sepesi, B; Swisher, S G; Vaporciyan, A A; et al.
Abstract: Background: Long-term survival outcomes of trimodal therapy (TMT; chemoradiation plus surgery) and bimodal therapy (BMT; chemoradiation) have seldom been analysed. In a selective-surgery paradigm, the benefit of TMT in patients with a complete clinical response is controversial. Factors associated with survival in patients with a clinical complete response to chemoradiation were evaluated. Methods: Patients with stage II–III oesophageal squamous cell carcinoma treated with TMT or BMT from 2002 to 2017 were evaluated. The BMT group consisted of patients who were otherwise eligible for surgery but underwent chemoradiation alone followed by observation. This group included patients who later had salvage oesophagectomy. Survival was evaluated and compared between TMT and BMT groups. Elastic net regularization was performed to select co-variables for Cox multivariable survival analysis in patients with a clinical complete response. Results: Of 143 patients, 60 (41.9 per cent) underwent TMT and 83 (58.0 per cent) BMT. Patients who underwent TMT had longer median overall survival than those who had BMT (77 versus 33 months; P = 0.019). For patients with a clinical complete response, TMT achieved longer median overall survival than BMT (123 versus 55 months; P = 0.04). BMT had a high locoregional recurrence rate (48 versus 6 per cent; P < 0.001); 26 of 29 patients with locoregional recurrence in the BMT groupunderwent salvage resection. Cox multivariable analysis demonstrated that upper–mid oesophageal tumour location (hazard ratio (HR) 2.04; P = 0.024) and tumour length (HR 1.18; P = 0.046) were associated with worse survival. Although TMT was not associated with survival, it was a predictor of reduced recurrence (HR 0.28; P = 0.028). The maximum standardized uptake value after chemoradiation also predicted recurrence (HR 1.33; P < 0.001). Conclusion: In patients who achieve a clinical complete response, TMT reduces locoregional recurrence but may not prolong survival. The differences in survival outcomes may be due to patient selection; therefore, a selective-surgery strategy in oesophageal squamous cell carcinoma is a reasonable approach. Abstract : For locally advanced oesophageal squamous cell carcinoma treated in a selective-surgery paradigm, patients who achieved a clinical complete response after chemoradiation had better overall survival and lower recurrence rates with trimodal compared with bimodal therapy. However, factors associated with overall survival were upper–mid oesophageal tumour location and tumour length, suggesting that these factors, rather than trimodal versus bimodal therapy, were significant predictors of overall survival.